The Javanese People’s Attitude Towards Sundanese Language - Septiani Rahmawati (Passage, 2013)
The present study entitled The Javanese People’s Attitude towards Sundanese Language aims to find out the Javanese people’s attitude towards Sundanese language and their reasons to have such attitude. This research is a case study which involved five Javanese people working in a catering service company in Bandung as the respondents of the study. Data were collected from observation, questionnaires, and interviews. To analyze the data, some theories were applied; the theory proposed by Garret (2010) was utilized to analyze the components of language attitude that determine whether the attitude is positive or negative, whereas the theory from Holmes (2001) was employed  to investigate the reasons why they have such  attitude. Based on the data analysis result, it shows that the respondents tend to communicate in Sundanese language in their daily conversation. It also can be seen from the percentage of Sundanese language they used (28.06%) indicating that it is higher than the percentage of Javanese language used (3.96%). Regarding to the respondents’ attitude towards Sundanese language, the findings refer that most of them have positive attitude due to their approval to use Sundanese language in their daily conversation. Keywords: Javanese, Attitude, Sundanese Language